Investigating the English vocabulary needs, exposure, and knowledge of isiXhosa speaking learners for transition from learning to read in the Foundation Phase to reading to learn in the Intermediate Phase : a case study - Sibanda, Jabulani (Rhodes University, Faculty of Education, Department of Education, 2014)
The nature of learners' transition from Grade 3 to Grade 4 has serious and far reaching ramifications for their educational success in the subsequent grades. This is true of the South African education system, as it is for several other education contexts. The challenge that complicates the transition is largely a lexical one. It is with that understanding that the present study aimed to do three things namely: to determine the vocabulary needs of Grade 3 learners for transitioning to Grade 4; to establish the extent to which Grade 3 isiXhosa speaking learners are exposed to, and prepared for, the acquisition of that requisite vocabulary; and to establish the extent of Grade 4 learners' knowledge of that vocabulary at the beginning of the year. The vocabulary needs of Grade 3 learners for the transition to Grade 4 were determined from the Grade 4 subject textbook corpus. Word frequency was the criterion used to determine the usefulness and critical importance of a word for the transition. The AntConc concordance software program was used to generate word frequencies. Words with high frequency across the different subject areas, which were confirmed as high frequent in four other known word lists, were considered as constituting the vocabulary needs of learners at the verge of this significant transition. The extent of learners' preparedness for transitioning to Grade 4 in terms of their vocabulary exposure and vocabulary instruction was determined through teacher interviews, classroom observations, analysis of teacher classroom talk, analysis of the exposure and recycling of high frequent vocabulary in Grade 3 reading materials and classroom print. From these diverse sources, findings point to a paucity in both the exposure and recycling of the requisite vocabulary in these sources of classroom language input. Classroom observations and teacher interviews attest to lack of deliberate vocabulary instruction in the Grade 3 English First Additional Language lessons. The only extensive coverage of the requisite vocabulary was in the Grade 3 reading materials which included Big books, Readers and Workbooks. The Grade 4 learners' knowledge of the 60 high frequency words was tested through nine vocabulary tests, three of which tested their knowledge of word recognition, three tested passive word knowledge and the remaining three tested learners' active word knowledge. All the Grade 4 learners in the ten participating schools (297) were tested. Performance in the tests indicated that Grade 4 learners' knowledge of words requisite for reading to learn was low. That observation was consistent with an analysis of learners' performance per school, per district, per word, per test and per word bands. Tests of word recognition were done better than those of passive word knowledge and active word knowledge. Particularly problematic was test 4 which tested learners' knowledge of definition of words.
Keywords: Uncatalogued